CHALLENGES IN OVERCOME DEVIANT TEACHING IN THE ERA OF DIGITAL TECHNOLOGY: AN ANALYSIS FROM THE PERSPECTIVE OF ISLAMIC AND CIVIL LAW IN MALAYSIA (SALAM Digest: Syariah and Law Undergraduate Symposium, 2023)
The development of digital technology is encountering a growing phase whereby it is frequently utilized as a communication tool and information exchange process that provides goods towards society locally and internationally. Along with the advancement of technology it allows the chances of deviant teaching to spread among the society. However, there is no specific law or provision that govern the deviant teaching neither in syariah or civil law to control the deviant teaching cases in Malaysia. Besides that, the objective of this research study is to understand the challenges to overcome deviant teaching through existing syariah and civil law, to analyze the mechanism to restrict deviant teaching in cyberspace based on maqasid syariah and suggest the improvement for syariah and civil law to vanquish deviant teaching in our country. Furthermore, this finding study applies qualitative method that consist of field study and library research such as interview session and reading journal articles. Therefore, it is important to discover the relation between existing laws in Malaysia with the deviant teaching issue that occur in cyberspace whereby the government may exercise the new approach or action to reduce the influence of deviant teaching among society and protect the aqidah of Muslims in our country.